2018
DOI: 10.1111/trf.15011
|View full text |Cite
|
Sign up to set email alerts
|

The association between blood donor sex and age and transfusion recipient mortality: an exploratory analysis

Abstract: BACKGROUND There is recent support for long‐term adverse effects of donor‐recipient sex‐mismatched red blood cell (RBC) transfusion, but short‐term impact is unknown. A retrospective exploratory analysis was performed using data from a research database. METHODS Adults admitted to hospitals in one Canadian center who received RBCs (2008–2014 [3 sites]; 2012–2014 [1 site]) were eligible. Patient data were extracted from a research database and donor data from the blood supplier. Cox regression models were used,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
105
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(115 citation statements)
references
References 26 publications
(53 reference statements)
6
105
4
Order By: Relevance
“…While it appears that older donors can donate without undue health or safety risks to themselves, it is important to consider the quality and safety of the products donated by these donors and any implications for the recipients. Researchers have reported that exposure to RBCs from donors aged 45 years or younger are associated with increased patient mortality compared to blood from older donors; although others have interpreted the available evidence as indicating that the age of donors of RBC units is unlikely to impact the survival of patients receiving a transfusion . Research into the impact of donor age on RBC storage is under way, with suggestions that a predisposition to oxidative hemolysis is modulated by donor age .…”
mentioning
confidence: 99%
“…While it appears that older donors can donate without undue health or safety risks to themselves, it is important to consider the quality and safety of the products donated by these donors and any implications for the recipients. Researchers have reported that exposure to RBCs from donors aged 45 years or younger are associated with increased patient mortality compared to blood from older donors; although others have interpreted the available evidence as indicating that the age of donors of RBC units is unlikely to impact the survival of patients receiving a transfusion . Research into the impact of donor age on RBC storage is under way, with suggestions that a predisposition to oxidative hemolysis is modulated by donor age .…”
mentioning
confidence: 99%
“…From this perspective, it is interesting to note that Heddle et al . found increased signal from sex mismatch in the direction of male donor red cells to female recipients .…”
Section: Discussionmentioning
confidence: 86%
“…1 to ≤12 years) was included in 6 studies . An increased short‐term mortality signal was noted in two studies (Middelburg et al . did not demonstrate an increase in mortality until 90 days ).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted secondary analyses of donor age and hemoglobin levels, stratifying by donor sex, given known differences in hemoglobin levels by sex and the results of previous publications. 2,3 Because the number of transfusions was one of the stratifying variables, comparisons were done only between patients who received the same number of transfusions. The data were set up for analysis using the Andersen-Gill counting process format using the publicly available Stratify macro.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…mortality, while other studies finding no such associations. [1][2][3][4][5][6] Differences in the studied sample size, proportions of missing data, and statistical methods may explain these variable results. 7 However, there may be other blood donor characteristics, not previously accounted for, that have relevance to mortality of transfusion recipients.…”
mentioning
confidence: 99%